The Effect of Yeast, NPK and Fermentation Time in Bioethanol Fermentation from “Abacaxi” Pinapple Pericarp - Nery Sofiyanti; Dyah Iriani; Putri Intan Wahyuni; Nurul Idani; Puji Lestari (Jurnal Biologi Tropis, 2022)
Bioethanol is promising alternative fuel due to its less effect to environment. It is produced from bio-sources, such plant materials. Yeast and NPK have been reported as the ingredients in affecting bioethanol fermentation. The aim of this study was to examined the effect of yeast and NPK in bioethanol fermentation using the pericarp of “Abacaxi” pinnapple cultivar (Ananas comosus cv. “Abacaxi”). The pericarp juice of “Abacaxi” pineapple was made by blending the fresh pericarp and aquadest (1 : 1.5). The juice was then mix with dry commercial yeast (1 g, 2.5 g and 5 gr) and NPK  (1 g, 2 g, 3 g). A total of 9 treatments were used in fermentation.  Each treatment was replicated three times, brought the total sample was 27. The percentage of bioethanol for each treatment was measure using alcoholmeter for six days (24 h, 48 h, 72 h, 96 h, 120 h and 144 h). The result show that the percentage of bioethanol produced in this study varies among different treatment and fermentation time. Yeast and NPK gave significant effect in bioethanol fermentation, with the combination of 5 g yeast and 3 g NPK gave the highest percentage of bioethanol in 144 h of fermentation. Based on the result of this study, the pericarp of “Abacaxi” pineapple is potential bio-source for bioethanol fermentation.